Simultaneous Prediction of Morphologies of a Critical Nucleus and an Equilibrium Precipitate in Solids (Communications in Computational Physics, 2010)
We investigate the critical nucleus and equilibrium morphologies duringprecipitation of a second-phase particle in a solid. We show that a combination ofdiffuse-interface description and a constrained string method is able to predict boththe critical nucleus and equilibrium precipitate morphologies simultaneously withouta priori assumptions. Using the cubic to cubic transformation as an example, it isdemonstrated that the maximum composition within a critical nucleus can be eitherhigher or lower than that of equilibrium precipitate while the morphology of an equilibriumprecipitate may exhibit lower symmetry than the critical nucleus resulted fromelastic interactions.